Sex Differences in Latency and Amplitude Changes for Binaural Stimulation in Auditory Brain-stem Responses - ANUJ THAPHER (Journal of All India Institute of Speech and Hearing, 1970)
The study was carried out in a sound treated room of Audiology Department, AIISH, Mysore. Thirty-two normal hearing (20 dB HL ANSI 1969) subjects in the age range of 18 years to 28 years 2 months (mean age 20 years, 9 months). Subjects were divided into 2 groups, Group-I and Group-II. Group-I consisted of 16 malesand Group-II consisted of 16 females. As stated in the methodology the subjects were in supine position and 3 electrodes were used, active, ground and reference. ERATA-1000 was used. Logon stimulus was presented through the earphones. The frequencies of the Logon stimuli used were 2 KHz and 4 KHz. These stimuli were presented for 2048 times at a rate of 20 times/sec. 10 msec, sample time was used, The intensity of Logon stimulus was 80 dB HL.